Optimisation of process parameters for energy-efficient electro-hydraulic forming of Al-Mg alloy sheets. Issue 3 (2nd July 2020) - Ahmed, Meraj; Shrivastava, Archit; Kumar, D. Ravi; Nabi, Mashuq Un
ABSTRACT: Electrohydraulic Forming (EHF) is a high strain rate-forming process which has potential applications in manufacturing of sheet metal parts. In EHF, the energy from a charged capacitor bank is delivered to the workpiece through a fluid medium. In the present work, an experimental setup has been developed for bi-axial stretching of sheets (free bulging) with a 5.25 kJ capacitor bank. It has been established that the important process variables are stand-off distance (SOD), wire diameter, electrode gap (EGAP), and the medium through which the energy is transferred. For the given die set-up and bank, three levels of SOD, EGAP, and wire diameter have been used to study the effect of these parameters on formability of AA5052 alloy sheets. The compressibility of the medium affects the propagation of shock wave and hence water and oil have been used in this work. Variation in wire diameter and electrode gap influences the pulse characteristics and hence formability. Formability was determined by conducting limiting dome height tests using full factorial design of the experiments. Maximum dome height has been obtained with the smallest EGAP and intermediate values of SOD and wire diameter.